Greening Greensburg: Affordable and sustainable home designs - Gabbard, Todd; Coates, Gary (Kansas State University, 2009)
On May 4, 2007 an EF5 tornado, nearly two miles wide and packing winds of up to 205 miles per hour, cut a swath through Greensburg, KS, leveling 95% of the town’s buildings and leaving the rest of them uninhabitable. Miraculously only twelve people were killed by this twister. With full support from Governor Kathleen Sebelius, various agencies of the Federal government, the community decided to rebuild as a model sustainable community for the twenty-first century. Perhaps the most daunting challenge facing Greensburg, however is building affordable, beautiful and sustainable housing. During the fall semester 2008 students in Professor Coates’ graduate design studio focused on the design of net zero energy green homes for the reconstruction process. The client included: 1) an Advisory Board comprised of town officials, members of Greensburg Greentown (a non-profit agency dedicated to rebuilding the town sustainably), area residents, and representatives of the business community Greensburg Greentown (a non-profit Organization), and; 2) Xtreme Homes (a manufacturer of Leed certified SIPS panels and modular housing, that is planning to locate a factory in Greensburg within the next year). Xtreme Homes is committed to building a selection of the student-designed homes in the Greensburg factory for citizens of the community who choose them. Once built these dwellings will serve as a “living laboratory” for sustainable design and construction and a central part of the plan to create the greenest community in America. Two major project outcomes were produced by the studio: 1) A pattern book presenting by means of text, drawings and model photographs, a diverse range of green residential designs, and; 3) An exhibition in Greensburg of drawings and models of the proposed design alternatives. The presentation will present the student designs, summarizing their sustainable design and livability features.
Keywords: Greensburg (Kan.); Sustainable housing; Xtreme Homes; Home designs; Sustainable design